Engaging the spirit world in modern Southeast Asia - Lauser, Andrea.; Endres, Kirsten W. (Asian anthropologies ;, 2011)
"'The world today is as furiously religious as it ever was.' This quote from Peter Berger now appears to be undisputed in the contemporary social and cultural sciences. A look around the globe reveals that modernization does not necessarily lead to a decline of religion, neither in society nor in the minds of individuals. Moreover, the multifaceted and divergent responses to modernization processes have significantly contributed to a critical reflection on the notion of a singular modernity, and as a result it has been suggested to speak of multiple, vernacular, alternative, or "other" modernities. Southeast Asia in particular presents a rich field of inquiry into the dynamics of these "modernities" that have produced and shaped a wide variety of religious phenomena. With case studies from Indonesia, Malaysia, Thailand, Myanmar, and Vietnam, these contributions reveal contemporary religious practices in Southeast Asia as thoroughly modern manifestations of uncertainties, moral disquiet and unequal rewards in the contemporary moment."--Publisher's description.